Functional Analysis of Rare Genetic Variants in the Negative Regulator of Intracellular Calcium Signaling RCAS/SLC10A7 - Wannowius, Marie; Karakus, Emre; Geyer, Joachim (Frontiers in Molecular Biosciences, 2021)
The solute carrier family 10 member SLC10A7 is a negative regulator of intracellular calcium signaling (RCAS). In cell culture, SLC10A7 expression is negatively correlated with store-operated calcium entry (SOCE) via the plasma membrane. SLC10A7-deficient cells have significantly increased calcium influx after treatment with thapsigargin for depletion of ER calcium stores, whereas SLC10A7/RCAS overexpression limits calcium influx. Genetic variants in the human SLC10A7 gene are associated with skeletal dysplasia and amelogenesis imperfecta and reveal loss of function on cellular calcium influx. More recently, an additional disease-related genetic variant (P303L) as well as some novel genetic variants (V235F, T221M, I136M, L210F, P285L, and G146S) have been identified. In the present study, these variants were expressed in HEK293 cells to study their subcellular localization and their effect on cellular calcium influx. All variants were properly sorted to the ER compartment and closely co-localized with the STIM protein, a functional component of SOCE. The variants P303L and L210F showed significantly reduced effects on cellular calcium influx compared to the wild-type but still maintained some degree of residual activity. This might explain the milder phenotype of patients bearing the P303L variant and might indicate disease potential for the newly identified L210F variant. In contrast, all other variants behaved like the wild-type. In conclusion, the occurrence of variants in the SLC10A7 gene should be considered in patients with skeletal dysplasia and amelogenesis imperfecta. In addition to the already established variants, the present study identifies another potential disease-related SLC10A7/RCAS variant, namely, L210F, which seems to be most frequent in South Asian populations.